2001
DOI: 10.1103/physrevlett.86.3411
|View full text |Cite
|
Sign up to set email alerts
|

Standing Optical Phonons in Finite Semiconductor Superlattices Studied by Resonant Raman Scattering in a Double Microcavity

Abstract: We report optical double resonant enhancement of Raman scattering in a new double microcavity geometry. The design allows almost backscattering geometries, providing easy access to the excitations' in-plane dispersion. The cavity is used to study the phonon spectra of a finite GaAs/AlAs superlattice. A new type of "standing optical vibration" is demonstrated involving the GaAs confined phonons with a standing wave envelope determined by the superlattice thickness. A strong dispersion of the first order standin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…A similar coupling effect has also been observed in enhanced infrared spectroscopy [16,17]. Compared to the SERS effect, the bulk enhancement effect is more capable of embodying the nature of the material and therefore, attracts an increasing attention in investigating new materials especially with the scaled-down size, in particular nanoparticle substrates [15].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…A similar coupling effect has also been observed in enhanced infrared spectroscopy [16,17]. Compared to the SERS effect, the bulk enhancement effect is more capable of embodying the nature of the material and therefore, attracts an increasing attention in investigating new materials especially with the scaled-down size, in particular nanoparticle substrates [15].…”
Section: Introductionmentioning
confidence: 84%
“…The latter brings SERS into the forefront with single-molecule spectroscopy [3,4]. SERS is concerned with the molecular vibration of surface species, while there is still another less-known Raman enhancement effect which is chiefly concerned with the lattice vibration of the bulk substrate itself, such as semiconducting or insulating materials [5][6][7][8][9][10][11][12][13][14][15]. This enhancement is mostly due to the coupling of the laser radiation and Stokes photons with microcavities [6][7][8][9][13][14][15].…”
Section: Introductionmentioning
confidence: 98%
“…Extending these ideas from photon confinement to confinement of vibrational waves, we propose a planar ''phonon cavity'' structure designed to confine acoustical phonons. In addition, we show theoretically that Raman scattering through an optical cavity geometry [2,3] is able to probe these novel excitations, and we demonstrate their existence through experiments in a real GaAs=AlAs based structure. These results are relevant to diverse phenomena as, e.g., phonon amplification and stimulated emission [4 -6], coherent generation and control of phonons [7], and modified electron-phonon interactions.…”
mentioning
confidence: 96%
“…We have shown that this photon confinement can be exploited, for instance, to obtain hugely enhanced ( 10 5 ) Raman cross sections in double optical resonant geometries [2]. Such Raman scattering geometries have lead to novel phonon physics, including the observation of standing optical phonons in finite-size multiple quantum wells [3].…”
mentioning
confidence: 98%
“…If the two levels interact repulsively, then the energies of each will be perturbed so as to avoid crossing each other. Such a phenomenon is not rare in semiconductor physics and has been observed between two vibrational modes 41,42 , two electronic transitions 43,44 , and between an electronic transition and a vibrational mode [45][46][47][48][49] . Whether or not the two levels interact is determined by their symmetries and the requirement of the conservation of energy.…”
Section: Experimental Techniquesmentioning
confidence: 98%